Evaluation and treatment of shoulder instability - Anakwenze, O. A.; Huffman, G. R. (The Physician and Sportsmedicine, 2011)
The shoulder joint has a wide range of motion as a result of a complex interplay of soft tissue and bone structures. It is also the most frequently dislocated joint in the body. Shoulder dislocations are generally classified as traumatic and nontraumatic. There are many specific causes, each of which necessitate individualized treatment modalities. Accurate diagnosis requires a careful history and physical examination. Arthroscopic surgery and advances in imaging have expanded our understanding of anatomy and pathology relevant to shoulder instability and its treatment. Surgery is the treatment of choice for recurrent traumatic instability. Surgery may also be indicated in some first-time traumatic dislocations in young contact athletes, whereas rehabilitation is the initial treatment of choice in older patients with initial instability and in those with nontraumatic dislocations. Results of arthroscopic capsulolabral repair now equal those of open capsulolabral repair and have become the surgical treatment of choice for most patients. However, in cases of recurrent instability and significant bone deficiency of either the glenoid or humeral head, open bone reconstructive procedures are often necessary to ensure successful outcomes.